Intensive Blood Pressure Targets for Diabetic and Other High-Risk Populations: A Pooled Individual Patient Data Analysis. Issue 5 (May 2018) - Aggarwal, Rahul; Steinkamp, Jackson; Chiu, Nicholas; Petrie, Benjamin; Mirzan, Haares
Abstract : Optimal blood pressure (BP) targets for different populations, especially diabetics, remain uncertain after conflicting data on intensive management. We assessed whether a <120 mm Hg systolic target is beneficial and whether certain patient populations differ in response. Individual patient data of 14 094 patients from 2 randomized control trials was pooled. Seven thousand forty patients were assigned to an intensive target of <120 mm Hg and 7054 patients to a standard target of <140 mm Hg in an intention-to-treat analysis. The primary outcome was a composite of myocardial infarction, other acute coronary syndromes, stroke, heart failure, and cardiovascular mortality. Interactions between treatment and baseline characteristics were assessed. Secondary outcomes included nonfatal myocardial infarction, stroke, heart failure, cardiovascular mortality, and overall mortality. Intensive management significantly lowered primary outcome rate (hazard ratio, 0.83; 95% confidence interval, 0.74–0.92; P <0.001). No significant interaction was observed between treatment effect and diabetes mellitus status ( P =0.16). Significantly reduced secondary outcomes included stroke (hazard ratio, 0.75; P =0.033) and heart failure (hazard ratio, 0.76; P =0.014). No significant interactions were observed between treatment effect and baseline age, sex, race, cardiovascular disease history, systolic BP, or diastolic BP ( P values: 0.40, 0.95, 0.54, 0.18, 0.86, and 0.67, respectively). BP targets of <120 mm Hg improved cardiovascular outcomes. Diabetic patients responded similarly to this intervention, as did those with different age, sex, cardiovascular disease history, baseline BPs, and race. The intensive group had increased risk of intervention-related adverse outcomes (3.97% versus 1.53%; P <0.001). Clinicians should consider <120 mm Hg systolic targets for a variety of patients, including diabetics.